A First step in the direction to modifying gravity: scalar-tensor and f(R) theories - Bessa, Pedro; Ottoni, Túlio (Cadernos de Astronomia, 2022)
Today, after its triumphs, general relativity is considered a theory with viable modifications. In this review, we introduce in a pedagogical way the fundamentals of a class of theories that try to fill the gaps left by general relativity, the class of f(R) and scalar-tensor theories. We build the theories from the action principle and obtain their field equations. We also show the equivalence between the two theories and comment on the screening mechanism. At the end, we show some observational results on modifications of general relativity with these types of theory on mind.